Hidden Curriculum in Student Character Formation through Activities in Elementary School: A Case Study - Sukarni, Sukarni (Juwara: Jurnal Wawasan dan Aksara, 2025)
This study aims to explore the role of hidden curriculum in the development of character education in elementary schools. The method used was a qualitative approach with a case study design, involving 28 grade V students and 5 teachers from one of the elementary schools in Bojonegoro. Data was collected through in-depth interviews with students and teachers to explore their understanding of the influence of activities outside of formal learning on character building. The results of the study show that social, cultural, sports, and extracurricular activities carried out in schools have an important role in instilling values such as discipline, cooperation, responsibility, and respect. The findings also reveal that teachers play a central role in managing hidden curriculum through their attitudes and interactions with students. This study concludes that hidden curriculum contributes significantly to the formation of student character, and it is important for schools to plan these activities systematically to support character education. Theoretically, this research highlights the importance of integrating hidden curriculum into character education frameworks, while practically offering insights for educators to design and optimize school activities that foster character development.